2016
DOI: 10.1556/1846.2016.00013
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Enhanced Efficiency in the Synthesis of α-Diazosulfoxides by Exploiting the Process Control Enabled in Flow

Abstract: Continuous-flow generation of α-diazosulfoxides results in a two-to three-fold increase in yields and decreased reaction times compared to standard batch synthesis methods. These high yielding reactions are enabled by flowing through a bed of polystyrene-supported base (PS-DBU or PS-NMe 2 ) with highly controlled residence times. This engineered solution allows the α-diazosulfoxides to be rapidly synthesized while limiting exposure of the products to basic reaction conditions, which have been found to cause ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Moreover, the used of the continuous process in these reactions minimized the risks associated with handling hazardous and explosive reagents on large scale (Deadman et al 2016). This group also studied the continuous-flow generation of α-diazosulfoxides using a bed of polystyrenesupported base (PS-DBU or PS-NMe2), a safe diazo transfer reagent dodecylbenzenesulfonyl azide (DBSA) and a high control of the residence times (McCaw et al 2016). With the results of these studies, they could synthesize several novel α-diazo-β-keto sulfoxides at higher yields and at shorter reaction times than batch conditions (McCaw et al 2017) ( Figure 28).…”
Section: Diazo Transfer Reactionmentioning
confidence: 99%
“…Moreover, the used of the continuous process in these reactions minimized the risks associated with handling hazardous and explosive reagents on large scale (Deadman et al 2016). This group also studied the continuous-flow generation of α-diazosulfoxides using a bed of polystyrenesupported base (PS-DBU or PS-NMe2), a safe diazo transfer reagent dodecylbenzenesulfonyl azide (DBSA) and a high control of the residence times (McCaw et al 2016). With the results of these studies, they could synthesize several novel α-diazo-β-keto sulfoxides at higher yields and at shorter reaction times than batch conditions (McCaw et al 2017) ( Figure 28).…”
Section: Diazo Transfer Reactionmentioning
confidence: 99%
“…The use of Dowex resin 16 offered a number of advantagesin addition to the more rapid formation of tosyl azide, it was evident that complete elution of the tosyl azide 12 from this resin was more efficient than from Amberlite resin 15 , as evidenced by subsequent washings of the used resins and the differing conversion efficiencies. This protocol for the generation and use of a sulfonyl azide in a water-free reaction stream is a significant addition to our approaches for diazo transfer in flow, opening up diazo transfer to less acidic substrates such as aryl acetates, in addition to the advantage of introducing the azide to the process in a resin form.…”
Section: Resultsmentioning
confidence: 99%
“…The exploitation of α-diazocarbonyl chemistry has been a key beneficiary of advances in continuous processing. , Continuous methodologies for the generation of diazomethane have been reported, including the use of tube-in-tube reactors . Furthermore, generation and use of sulfonyl azides in continuous flow has been demonstrated, obviating the requirement to isolate and handle these potential hazardous reagents. , While the Regitz diazo transfer from sulfonyl azides is a remarkably efficient and generally applicable process working with a wide variety of acceptors, the hazards associated with use and handling of sulfonyl azides are well documented. , While modified sulfonyl azides have been developed with improved safety profiles, none of these fully resolve the concerns in effecting diazo transfer at scale using a preprepared sulfonyl azide. ,, In recent years, our team has developed a number of protocols for in situ generation of sulfonyl azides followed by diazo transfer, together with telescoping with downstream reactions, including thermal Wolff rearrangement and ketene trapping, copper catalyzed C–H insertion and aromatic additions, and rhodium-mediated S–H insertion .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally the monocyclic α-diazo sulfoxides 5 – 7 were challenging to isolate as pure compounds but were present in low yields (<12%). With the synthetic routes to these α-diazo sulfoxides established in batch, and their syntheses achieved in moderate yields, in line with the dramatically enhanced yields from the lactone and lactam series utilizing continuous flow, this approach was next explored for the synthesis of the β-keto sulfoxide derivatives …”
Section: Results and Discussionmentioning
confidence: 99%
“…Currently, there is great interest in continuous flow processing for handling diazo compounds and the associated increased safety profile. Our research group has recently reported the ability to generate, use, and subsequently quench the explosive diazo transfer reagent tosyl azide in situ using continuous flow processing . This approach limits the amounts of hazardous compounds formed at any point in time and is extremely advantageous to making diazo chemistry more acceptable for broader use. Additionally, by taking advantage of the process control enabled in continuous flow, we have established a high-yielding diazo transfer methodology for the synthesis of lactone-derived α-diazo sulfoxides using the Regitz diazo transfer methodology and the relatively safe diazo transfer reagent dodecylbenzenesulfonyl azide (DBSA) ( Scheme ). …”
Section: Introductionmentioning
confidence: 99%